Analisis Kelayakan Investasi Mesin Printing Percetakan Offset untuk Meningkatkan Kapasitas Hasil Output pada PT. XYZ - Putri, Elvia Defitriana; Herlina, Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The aim of this research is to find out whether purchasing an offset printing machine is feasible or not. In problems One way to find out how much money an investment will generate for a company is to carry out financial analysis. The calculations used include: finding the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and OEE (Overall Equipment Effectiveness). This research was conducted at PT. XYZ, starting from February to July 2024. Field studies, interviews and data collection were carried out to analyze the feasibility of investing in an offset printing machine. Quantitative and qualitative analysis, such as OEE, Depreciation, NPV, IRR, and PP. The results demonstrate a worthy investment with a comprehensive picture of engine performance. The conclusion provides a clear view of the feasibility of the investment and directions for future business development. The analysis results show that the offset printing machine at PT. XYZ has an OEE below 85%, indicating that its efficiency is less than optimal. This suggests the need to replace machines with new ones to increase production effectiveness. In addition, the depreciation calculation shows an estimated depreciation cost of IDR 1,080,000,000 per year, which must be considered in long-term financial planning. However, the NPV results show that the investment is feasible with a value of IDR 227,607,149